Simulation of wheel type fuel grain in hybrid rocket motor - Azami, Muhammad Hanafi; Kafafy, Raed; Idres, Moumen (2013)
till today, with issues specifically related to combustion instability and lowered regression rate. Simulation is used as a tool to investigate the behavior of hybrid rocket grains under varied operating conditions. In this paper, we develop simulation algorithm and a code, which may also serve as a valuable teaching resource. The algorithm is based on a legacy interior ballistic model. The simulation code is used to simulate the combustion process of a wheel typed fuel grain in a hybrid rocket. We analyze the performance of the grain in terms of the transient behavior of rocket thrust, specific impulse and the regression rate. The performance of wheel-typed grain is compared with conventional multiple circular-port grains. MATLAB® environment was used to develop the simulation code, and visualize the temporal variation of performance characteristics and grain geometry during burning. A numerical simulation of hydroxyl-terminated polybutadiene (HTPB) solid fuel with liquid oxygen was used to analyze the performance of the hybrid rocket. Results show an increase of the regression rate and thrust-to-weight ratio on a wheel-typed grain design compared to multiple circular port grain design. The final area of each port also indicated that the fuel slivers are less in a wheel-typed grain. However, multiple circular ports displayed a much better performance in specific impulse. This also shown that the performance of a hybrid rocket has a strong dependence on the geometrical fuel grain design.